Rozum w służbie polityki, czyli demokracja i oświata w myśli markiza de Condorcet - Sochański, Tomasz (Filozofia Publiczna i Edukacja Demokratyczna, 2014)
This study aims to highlight the role of education in a democratic society in the political philosophy of Nicolas de Condorcet. Condorcet refuted legitimising political power on the idea of general will and postulated to replace it with the notion of reason and probability of truth. This assumption tightly linked the wellbeing of democracy with a public education system which, on the one hand, was to prepare citizens to take an active role in the public sphere, and on the other, allow them to improve the political system in which they function in accordance with the progress of the human spirit.